2010
DOI: 10.1063/1.3428476
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption spectrum in disordered semiconductor multilayers

Abstract: The effects of chemical disorder on the electronic and optical properties of semiconductor alloy multilayers are studied based on the tight-binding theory and single-site coherent potential approximation. Due to the quantum confinement of the system, the electronic spectrum breaks into a set of subbands and the electronic density of states and hence the optical absorption spectrum become layer-dependent. We find that, the values of absorption depend on the alloy concentration, the strength of disorder, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The results showed that, the photon absorption by the system is layer dependent and strongly changes by variation of the scattering-strength of the chemical impurities [21]. In the present study, we extend our previous approach [21] for the magnetic impurities at a paramagnetic temperature, and investigate the electronic and optical properties of DMS multilayers. To study the optical absorption spectrum in the presence of the magnetic impurities, we use the Onodera-Toyozawa theory [25], which is related to a binary mixed crystal or an alloy consisting of atoms (or molecules) A and B, in which the transition dipole moments of A and B atoms are equal.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…The results showed that, the photon absorption by the system is layer dependent and strongly changes by variation of the scattering-strength of the chemical impurities [21]. In the present study, we extend our previous approach [21] for the magnetic impurities at a paramagnetic temperature, and investigate the electronic and optical properties of DMS multilayers. To study the optical absorption spectrum in the presence of the magnetic impurities, we use the Onodera-Toyozawa theory [25], which is related to a binary mixed crystal or an alloy consisting of atoms (or molecules) A and B, in which the transition dipole moments of A and B atoms are equal.…”
Section: Introductionmentioning
confidence: 53%
“…With increasing x, the contribution of spin scattering by the localized spins in the scattering process of the carriers increases and the impurity band and hence, the whole electronic spectrum is broadened. This broadening which does not appear in LDOS of the NMS alloys [21] is a consequence of the localized spin fluctuation of magnetic impurities. It is evident that the strong exchange interaction splits the host band into two subbands.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations